Design and Validation of LexiPlay: A Multisensory Game-Based Application for Literacy Learning among Children with Dyslexia - Tetha Agustina, Menik; Pratama Irwin Talenta; M. Zakki Abdillah (Indonesian Journal of Learning Education and Counseling, 2026)
Children with dyslexia often experience difficulties in reading, spelling, and phonological processing, which may hinder their literacy development. Although various educational applications have been developed to support learning, many existing platforms do not sufficiently integrate multisensory learning principles and game-based features that are essential for supporting children with dyslexia. Therefore, this study aims to develop and validate LexiPlay, a multisensory game-based learning application designed to support literacy development among children with dyslexia, and to examine its validity and practicality as a learning medium. This study employed a Research and Development (R&D) approach based on the Borg and Gall model. Data were collected through observation, interviews, and documentation. The development process involved expert validation, instrument validation, individual trials, and small-group trials with students with dyslexia. The collected data were analyzed using both qualitative and quantitative approaches. The results indicate that the LexiPlay application achieved a “highly valid” classification based on expert evaluation and was considered “highly practical” based on limited field testing. The application integrates multisensory learning elements, gamification features, and a dyslexia-friendly interface, which contribute to improving student engagement and supporting early literacy learning. These findings suggest that LexiPlay has strong potential as an innovative digital learning tool to support literacy development in children with dyslexia and provide important implications for special education, inclusive education practices, and the development of evidence-based digital learning interventions.